Occurrence of shrimp species (Crustacea: Decapoda: Natantia: Penaeidea and Caridea) in Ubatuba Bay, Ubatuba, SP, Brazil - Da Costa, R. C. [UNESP]; Fransozo, A. [UNESP]; Mantelatto, F. L.M. [UNESP]; Castro, R. H. [UNESP] (My University, 2000)
The species composition of Penaeidea and Caridea shrimp was studied in Ubatuba Bay, Sao Paulo, Brazil. Samples were taken monthly from September 1995 to August 1996, using two double-rig trawling nets. A total of 21 marine shrimps species were obtained, belonging to eight families. Sergestoids were represented by a single species of Sergestidae, while penaeoids comprised three families, Penaeidae, Sicyoniidae and Solenoceridae. Caridea shrimps belonged to two superfamilies, the Palaemonoidea, represented by Palaemonidae; and Alpheoidea by three families, Alpheidae, Ogyrididae and Hippolytidae. Sicyonia laevigata Stimpson, 1871 and Nematopalaemon schmitti (Holthuis, 1950) represent first records in Sao Paulo State, Brazil.